Effects of drying temperature on hygroscopicity and mechanical performance of resin-impregnated wood. Issue 11 (1st August 2022) - Xu, Kang; Gao, Yulei; Zhang, Xiaomeng; Li, Zhonghao; Song, Shasha; Wu, Yiqiang; Li, Xianjun; Lu, Jianxiong
Abstract: To clarify the effects of drying temperature on the hygroscopicity and mechanical performance of MUF resin-impregnated wood, we investigated the water vapor adsorption capability, modulus of rupture (MOR), modulus of elasticity (MOE), and surface hardness of MUF resin-impregnated wood treated at 60, 80, 100, 120, 140 °C. Drying temperature can influence the hygroscopicity of MUF resin-impregnated wood. As temperature increased, hygroscopicity typically decreased, but the resin-impregnated wood hygroscopicity increased after treatment at 60 °C. Drying temperature has shown significant influence on the mechanical performance of MUF resin-impregnated wood (α = 0.01). Increasing the treatment temperature can enhance the mechanical performance of resin-impregnated wood. However, brittleness of the resin-impregnated wood increased after treatment at 140 °C. Characterization of FTIR and 13 C CP/MAS NMR indicate that higher drying temperature led to lower content of hydroxymethyl groups and more substituted reactive sites on the amino group. This refers to more complete dehydration condensation between the resin active groups, thereby increasing the crosslinking density of the resin, increasing the cohesive strength, and decreasing the hygroscopic groups.